Further results on nonlinear tracking control and parameter estimation for induction motors. (September 2017) - Verrelli, C.M.; Tomei, P.; Lorenzani, E.; Fornari, R.; Immovilli, F.
Abstract: The original contribution of this paper, which concerns induction motors with uncertain constant load torque and rotor/stator resistances, is twofold. The first innovative contribution relies on the experimental analysis of the latest theoretically-based sensorless/output feedback solutions to the problem of tracking rotor speed and flux modulus reference signals with the simultaneous estimation of the uncertain parameters. The second novel contribution is constituted by the proof of existence for a new adaptive local flux observer from rotor speed and stator currents/voltages, which, in its full-order or reduced-order-like versions, involves neither over-parameterizations nor non- a priori verifiable first order stator resistance identifiability conditions at steady-state.